Optimization of logistics processes in the company's warehouses - Wang, Wanli (Харківський національний автомобільно-дорожній університет, 2025)
In the working conditions of PJSC Interconditioner, the issue of warehouse logistics is relevant, since effective warehouse management, which is one of the main links in the logistics chain, directly contributes to the optimization of costs and increased productivity. The paper considers the theoretical and methodological foundations of warehouse logistics; provides a brief description and analysis of the activities of the warehouse of PJSC «Interkonditsioner»; a set of measures is developed to improve the organization and management of logistics processes at the warehouse of PJSC «Interkonditsioner»; a forecast of the socio-economic effectiveness of the proposed measures to optimize warehouse logistics is made.
Keywords: logistics; management; warehouse; stocks; warehouse logistics